Planarian nociception: Lessons from a scrunching flatworm - Reho, Guillaume; Lelièvre, Vincent; Cadiou, Hervé (Frontiers in Molecular Neuroscience, 2022)
In addition to being studied for their exceptional regeneration abilities, planarians (i.e. flatworms) have also been extensively used in the context of pharmacological experiments during the past century. Many researchers used planarians as a model system for the study of drug abuse because they display high similarities with the nervous system of vertebrates at cellular and molecular levels (e.g. neuronal morphology, neurotransmitter ligands and receptor function). This research field recently led to the discovery of causal relationships between the expression of Transient Receptor Potential ion channels in planarians and their behavioral responses to noxious stimuli such as heat, cold or pharmacological analogs such as TRP agonists, among others. It has also been shown that some antinociceptive drugs modulate these behaviors. However, among the few authors that tried to implement a full behavior analysis, none reached a consensual use of the terms used to describe planarian gaits yet, nor did they establish a comprehensive description of a potential planarian nociceptive system. The aim of this review is therefore to aggregate the ancient and the most recent evidence for a true nociceptive behavior in planarians. It also highlights the convenience and relevance of this invertebrate model for nociceptive tests and suggests further lines of research. In regards to past pharmacological studies, this review finally discusses the opportunities given by the model to extensively screen for novel antinociceptive drugs.